(untitled) (Pedagogy of Higher and Secondary Education, 2022)
In the article an author analyses the terms of the use of game on lessons for forming of responsible appeal of junior schoolboys to the studies, determines the location of game on a lesson, rules of organization and its lead through. By an author determines the levels of educational activity, which are instrumental in forming of responsible attitude toward studies.